CORPORATE COMMUNICATIONS: TO TEACH IMPOSSIBLE TO REGULATE - M. A. LUKASHENKO (Высшее образование в России, 2018)
The article examines the communicative competence as one of the key soft skills of a graduating student. It substantiates that knowledge of communicative technics and instruments becomes a meta-competence for a graduate that furthers development of his general cultural and professional competences. The article shows that several universal competences stated in the Federal State Educational Standards of Higher Education 3+ implicitly include the communicative competence. The article analyzes problems of unmanaged realization of corporate communications, both at institution of higher education and in any other organization, and gives ground to solving those problems by means of developing corporate standards of team interaction. Each problem is illustrated by a practical case study. The author gives specific regulations that can optimize time costs of communications, minimize reputational risk, normalize business processes. All proposals of the author are illustrated by examples from business practice.